Psyllium (Plantago ovata Forsk) in frozen banana pulp Influence on rheological, nutritional and sensory characteristics - Franco, Elisangela Aparecida Nazario (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2023)
A frozen banana pulp with functional properties was developed and characterized in this work. For this, 0 g, 3 g, 5 g and 7 g of psyllium in 100 g of banana pulp were added. The use of this fiber in industrialized products can contribute to the nutritional enrichment of the products and provide functional benefits already acknowledged, such as lowering LDL cholesterol, lowering blood glucose, increasing satiety and relieving constipation. According to the World Health Organization, vegetable consumption should be increased, as it reduces the risk of chronic diseases. The main purpose of this work was to incorporate psyllium in frozen banana pulp to develop a healthy product. The samples were evaluated through chemical analyses, rheological properties and sensory testing with Check-All-That-Apply questions (CATA). The addition of psyllium had a significant effect not only on the viscosity but also on the sensory and nutritional properties of the frozen banana pulp. This study indicated that the production of frozen banana pulp with psyllium is viable, as it has desirable nutritional and sensory characteristics which can contribute to the maintenance of health